Model assessing thermal changes during high temperature root canal irrigation. Issue 3 (5th August 2016) - Bartolo, Analise; Koyess, Edmond; Camilleri, Josette; Micallef, Christopher
Abstract : The main aim of root canal irrigation is to eliminate micro‐organisms. Sodium hypochlorite (NaOCl) is considered to be the ideal material and raising its temperature potentiates the antimicrobial activity. NaOCl may lead to localised tissue necrosis when extruded past the root apex. This study analyses the use of high temperature root canal irrigation as an alternative process for the elimination of microorganisms from the root canal system. An experimental set‐up was designed where a constant supply of heat was passed from a heat source through a copper wire inside the root canal. The data acquired together with known constants pertaining to enamel and dentine was used to numerically model the thermal changes in a tooth using a finite element method. Results obtained from the finite element thermal model of the tooth were repeatable and were validated with the experimental results. The thermo‐physical properties of the tooth were varied and convergence criteria met. The temperatures reached were below what has been reported to cause irreversible damage to the bone. This was further confirmed from a series of simulations that were undertaken. The temperatures achieved were suitable for the elimination of microorganisms during root canal therapy.